Information characteristics of sound emission from small unmanned aerial vehicles - Kartashov, V.M.; Oleynikov, V.N.; Sheyko, S.A.; Babkin, S.I.; Koryttsev, I.V.; Zubkov, O.V.; Anokhin, A.M. (Radiotekhnika, 2017)
The results of comparison of experimentally obtained information characteristics of sound signals of two types of small unmanned aerial vehicles (UAVs) - a quadrocopter and a monoplane are given. Studies have shown that the energy spectra of the signals have a significant region of broadband noise and pronounced harmonic components with frequencies of multiple rotational speeds of the screw. Even with averaging of the spectral estimates for the ensemble of samples, harmonics with frequencies up to 8 ± 10 kHz are confidently observed. With a large difference in the modes of the quadro copter engines, the spectral maxima are divided into severalones, which can be one of the most important factors for the UAV classification. The algorithm for operational recognition of UAV is described, which includes the formation of recognition features on the basis of spectral estimates for their orthogonal transformation and the decision rule based on the Dice criterion.